2018
DOI: 10.1152/ajpendo.00262.2017
|View full text |Cite
|
Sign up to set email alerts
|

The hepatokines fetuin-A and fetuin-B are upregulated in the state of hepatic steatosis and may differently impact on glucose homeostasis in humans

Abstract: The liver is a central regulator of whole body glucose, and lipid homeostasis and hepatokines, like fetuin-A, have been identified as markers and mediators of fatty liver-induced cardiometabolic risk. The closely related protein fetuin-B was shown to be upregulated in the fatty liver and to impact on glucose homeostasis in mice. In the present study we aimed to test the relevance of these findings in humans. In 55 subjects, hepatic mRNA expression of both hepatokines, fetuin-A and fetuin-B, associated positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 49 publications
7
62
0
Order By: Relevance
“…The regulation of hepatic fetuin-A secretion is incompletely understood (Haukeland et al, 2012). Previous research has reported that fetuin-A mRNA expression in the liver correlated positively with hepatic triglyceride content and homeostatic model of insulin resistance (HOMA-IR) and these associations remained significant after adjustment for BMI (Peter et al, 2018). These findings were supported by a cross-sectional study reporting higher fetuin-A in subjects with elevated liver fat content (Stefan et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…The regulation of hepatic fetuin-A secretion is incompletely understood (Haukeland et al, 2012). Previous research has reported that fetuin-A mRNA expression in the liver correlated positively with hepatic triglyceride content and homeostatic model of insulin resistance (HOMA-IR) and these associations remained significant after adjustment for BMI (Peter et al, 2018). These findings were supported by a cross-sectional study reporting higher fetuin-A in subjects with elevated liver fat content (Stefan et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…However, normal ranges reported among locations are variable, which complicates interpretation, and, more importantly, ALT values do not reliably differentiate NAFLD severity, or distinguish uncomplicated NAFLD from NASH in children or adults [ 13 , 15 , 16 ]. Several other potential circulating biomarkers have been proposed [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] but few have been tested in children with biopsy-proven NAFLD, or tracked over the course of treatment or disease progression [ 13 , 16 , 25 ].…”
Section: Clinical Pathophysiologymentioning
confidence: 99%
“…Fourth, we cannot preclude the possibility of reverse causality between serum Fetuin-B and atherosclerosis due to our crosssectional study design. Fifth, although Meex, Zhu and we all found significant association of serum Fetuin-B with liver steatosis 8,9,18) , Peter recently found serum Fetuin-B level did not correlate with liver fat content or insulin sensitivity 24) , therefore, more studies should be conducted in different populations before the consistent findings between Fetuin-B and liver steatosis has been reached. Sixth, we should acknowledge that although serum Fetuin-B is mainly from liver, it may also be from other organs, as Denecke et al suggested 25) .…”
Section: Discussionmentioning
confidence: 58%